Laboratory Evaluation of Modified Asphalts with Different Polymers - Loría Salazar, Luis Guillermo (2025)
The modification of asphalts with polymers from different varieties and origins is one of the most important tendencies of the present highways construction industry.  Polymer contributions to reological properties improvement of the asphalts have been extensively studied. However, each time that a new product is on the market, it is necessary to carry out an exhaustive analysis of the improvements that the polymer would be able to cause to the asphalt.  The asphalts classification methodology by performance has been constituted in the fundamental tool of analysis of asphalts; however, in the case of modified asphalts its rank of application is very limited, just as has been determined up to now. The main problem is that modified asphalts with different polymers can have the same performance, without being able to discern among the individual contribution of each polymer that would lead to choose the polymer that maximize the characteristics of the modified asphalt.  Today, the protocols established in the NCHRP 9-10, are implementing a series of new trials that will be able to consider which, of various modifying agents, can cause better reological asphalt conditions This: NCHRP 9-10 contribution is fundamental to determine with what polymer will be the binder performed better, given that in many cases, the selection of a modifier is based only in financial criteria, with a same performance. With this technology update, it will be able to do financial analysis considering how useful it will be to the highway.  This study was born with the main objective to analyze different polymers and its effect on base asphalts AC-20 and AC-30, and to determine the performance that each one has, with different polymer concentrations This information can be of great importance for highways builders to choose adequate options that the market has. The result of the first phase of this project can be found in the report LM-PL-PV-IN-18 -02 a.  In this second phase, the results of the analysis of the AC-30 asphalt are presented, mixed with 6 different modifying agents, and the classification of the final product will be performed by means of the classification by performance primarily, and subsequently, by means of the trials indicated by the protocol NCHRP 9-10: creep, fatigue and zero cut viscosity (Zero Shear Viscosity, ZSV, by its acronyms in English.